COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF THE USE OF MODERN ANTIMICROBIAL AGENTS FOR THE PROCESSING OF TEXTILE PRODUCTS FOR MILITARY CIVILIAN PURPOSES - NEGORUY, VITA; PARASKA, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Ensuring the microbiological safety of textile materials is a key task in areas where hygiene, durability and resistance to external influences are especially important, in particular in the production of military household, medical, children’s and special clothing. Traditionally, synthetic agents are used to impart antimicrobial properties, in particular silver compounds, quaternary ammonium compounds, etc., but their use is often accompanied by environmental risks, toxicity to the environment and the human body, as well as a decrease in efficiency due to the adaptation of microorganisms. In this context, there is growing interest in the use of biosurfactants – particularly glycolipids, lipopeptides, and phospholipids – produced by various types of microorganisms, as an environmentally safe alternative. This study investigates the effectiveness of bio-based surfactants in providing antimicrobial properties to textile products. The mechanisms of antimicrobial action of biosurfactants are analyzed – in particular, the destruction of the cell membrane, disruption of metabolic processes and the ability to inhibit biofilm formation, as well as the spectrum of action of biosurfactants in relation to gram-positive, gram-negative bacteria and fungal pathogens. The comparative characteristic of antimicrobial efficacy of biosurfactants and traditional synthetic antimicrobial agents is presented. The expediency of using biosurfactants in the creation of functional textiles with a long-term antimicrobial effect, corresponding to the principles of circular economy, concepts of green chemistry and sustainable development, has been substantiated.